Nucleotide sequence of a cloned duck hepatitis B virus genome: comparison with woodchuck and human hepatitis B virus sequences. - Mandart, E (1984)
The nucleotide sequence of an EcoRI duck hepatitis B virus (DHBV) clone was elucidated by using the Maxam and Gilbert method. This sequence, which is 3,021 nucleotides long, was compared with the two previously analyzed hepatitis B-like viruses (human and woodchuck). From this comparison, it was shown that DHBV is derived from an ancestor common to the two others but has a slightly different genomic organization. There was no intergenic region between genes 5 and 8, which were fused into a single open reading frame in DHBV. Genes for the surface and core proteins were assigned to open reading frames 7 and 5/8. Amino acid comparisons showed some structural relationship between gene 6 product and avian reverse transcriptase, suggesting either evolution from a common ancestor or convergence to some particular structure to fulfill a specific function. This should be correlated with the synthesis of an RNA intermediate during DNA replication. This is also taken as an argument in favor of the hypothesis that gene 6 codes for the DNA polymerase that is found within the virion. DNA sequence comparison also showed that the two mammalian hepatitis B viruses are more homologous to each other than they are to DHBV, indicating that DHBV starts to evolve on its own earlier than the two other viruses, as do birds compared with mammals. From this it is proposed that the viruses evolved in a fashion parallel to the species they infect.